A simplified method for determining erythrocyte pyrimidine 5'-nucleotidase (P5N) activity by HPLC and its value in monitoring lead exposure. Issue 12 (December 1986) - Sakai, T; Ushio, K
Abstract : The method for determining erythrocyte pyrimidine 5'-nucleotidase (P5N EC 3.1.3.5) activity has been simplified using an automated high performance liquid chromatograph (HPLC). The activity determined by the simplified method agreed closely with that obtained by conventional methods. In 161 lead workers P5N activity declined linearly with increasing blood lead concentrations (Pb-B) between 20 and 80 micrograms/100 g, and correlated well with Pb-B (r = -0.87). For the same group of workers, correlation coefficients between Pb-B v ALA-D activity, zinc protoporphyrin, ALA-U, and coproporphyrin were -0.87, 0.73, 0.70, and 0.32, respectively. At Pb-B greater than or equal to 40 micrograms/100 g, the validity of P5N (1.86 at a cut off of 10 less than or equal to units) was higher than that of other indicators examined. P5N activity was fairly stable during the storage of samples for two weeks at 4 degrees C. Determination of P5N activity by this method may be a useful indicator in screening for moderate exposure to lead.